Neem made more effective - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The leaves and seeds of the neem tree are well known for their insecticidal properties. Scientists in the USA are boosting the toxicity of the active compound so that it will work more effectively. Indian farmers have for centuries used neem...